Chronic obstructive pulmonary disease and exacerbations: clinician insights from the global Hidden Depths of COPD survey. (April 2014) - Barnes, N.; Calverley, P.M.A.; Kaplan, A.; Rabe, K.F.
Abstract Objective: This real-life, global study aimed to investigate current views of and clinical practice in the management of COPD and its exacerbations, among clinicians from both the primary and secondary care settings. Methodology: We devised an online questionnaire about COPD management and invited 13, 613 general practitioners (GPs) and respiratory specialists to respond. Participating clinicians, recruited from an established research panel, treated a minimum of 10 (GPs) or 20 (respiratory specialists) patients with COPD per month. Completed responses were collected from 1400 clinicians from 14 countries. Results: A third of GPs and respiratory specialists reported that the main goal of COPD management was to improve patients' quality of life; only 14% of GPs thought that the prevention of exacerbations was a priority. The study showed a strong preference for inhaled corticosteroids in combination with other treatments, rather than as sole therapy, in line with global guidelines. Fewer GPs than respiratory specialists routinely recommended anticholinergics, pulmonary rehabilitation or oxygen therapy. Clinicians reported that 55% (GPs) and 57% (respiratory specialists) of their COPD patients had experienced an exacerbation in the previous 12 months. Although higher than those reported in clinical trials, these rates were lower than patients' own estimates from a corresponding patient survey, even in mild COPD patients (62%; 80% in severe patients). Despite this, 74% of GPs and 67% of respiratory physicians reported satisfaction with therapies to prevent exacerbations. Conclusions: This global survey revealed that clinicians' main goal when managing COPD was to improve the lives of their patients, and that few viewed reducing exacerbations as a priority. Despite a relatively high level of adherence to treatment recommendations, it appears that clinicians, particularly GPs, underestimate the frequency and impact of exacerbations. These results suggest a need to raise awareness of exacerbations among both GPs and respiratory specialists.